Self-employment and labor market risks - Richard Audoly (Institute for Fiscal Studies (IFS), 2024)
I study the labor market risks associated with being self-employed. I document that the self-employed are subject to larger earnings fluctuations than employees and that they frequently transition into unemployment. Given the self-employed are not eligible to unemployment insurance, I analyze the provision of benefits targeted at these risks using a calibrated search model with (i) precautionary savings, (ii) work opportunities in paid- and self-employment, (iii) skill heterogeneity. This exercise suggests that extending the current US unemployment insurance scheme to the self-employed comes with a clear increase in the transition rate from self-employment to unemployment and an unequal benefits to contributions ratio across skill groups. At the calibrated parameters, the self-employed in the middle of the skill distribution lose welfare.
Keywords: D11; D12; D14; E21; 330; Self-employed; Labor market; Risk; Unemployment; Unemployment insurance; Income; Welfare analysis; USA; Selbstständige; Arbeitsmarkt; Risiko; Arbeitslosigkeit; Arbeitslosenversicherung; Einkommen; Wohlfahrtsanalyse; USA